(untitled) (Revista Lusófona de Educação, 2026)
Here should be the abstract of the article written in English The objective of this study was to identify the perceptions, challenges, and training needs of public school teachers regarding the inclusion of students with Autism Spectrum Disorder (ASD). The research adopted a qualitative approach based on content analysis. Data were collected through a questionnaire answered by 34 teachers from a municipal school network and analyzed across seven thematic axes: prior training, challenges faced, required support, strategies used, training needs, priority topics, and suggestions for improvement. The categories were defined based on recurring themes in the participants’ responses. The results indicate that both initial and continuing teacher education are perceived as insufficient, particularly concerning behavior management, curricular adaptations, and understanding the characteristics of ASD. The most frequently mentioned challenges include sensory crises, disruptive behaviors, difficulties with socialization, lack of specialized support, and the need to balance overall classroom demands with individualized attention. Teachers also highlighted the scarcity of adapted materials and adequate classroom environments. The study concludes that the inclusion of students with ASD depends on integrated policies involving teacher training, multiprofessional support, and structural investments. The findings contribute by revealing real teacher demands and offering insights that may guide more effective training initiatives and inclusive education policies.